2006
DOI: 10.1111/j.1460-2695.2006.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Some comments on surface cracks in rails

Abstract: A B S T R A C TThe present work considers the problem of whether a shallow angle surface crack on a rail may propagate either parallel or perpendicular to the surface. After referring to a classification of crack-like defects, a distinct surface crack with a typical length of 1 mm and more, inclined to the surface by an angle of approx. 30 • , is introduced. Then various strain and stress states are discussed (eigenstress, residual and load stress state) which may control the crack growth. Stress intensity fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…It is well known that residual stresses significantly affect the fatigue crack propagation behaviour . Macroscopic residual stresses can be considered as an additional applied static loading, and they change locally the stress ratio.…”
Section: Closure Mechanismsmentioning
confidence: 99%
“…It is well known that residual stresses significantly affect the fatigue crack propagation behaviour . Macroscopic residual stresses can be considered as an additional applied static loading, and they change locally the stress ratio.…”
Section: Closure Mechanismsmentioning
confidence: 99%
“…To date, most efforts have been devoted to analyzing the interaction of surface-crack and multiple cracks under linear-elastic and elastic-plastic fracture mechanics regimes (Leek and Howard 1996;Moussa et al 1999;Sethuraman et al 2003;Carpinteri et al 2004;Feng and Xu 2006;Fischer et al 2006). The existing studies on this issue are focused on the methodology of fracture parameter analysis to obtain a quantitative description on the interaction of multiple cracks (Murakami and Nemat-Nasser 1982;Krishnamurthy and Raju 1990).…”
Section: Introductionmentioning
confidence: 97%
“…Fischer et al . discussed factors determining the difference of rail steels concerning cracks . They concluded that tensile strength alone is not sufficient to explain the difference in performance in field trials of head hardened grades and normal pearlitic grades, for example 900A seen by Heyder and Girsch .…”
Section: Introductionmentioning
confidence: 99%